La Charte de la langue française - Prujiner, Alain (Les Cahiers de droit, 1978)
This paper inderlines in a cursory way some questions of interpretation that seem to arise from Quebec's new Charter of the French Language.The Charter breaks new ground in legal terminology. Some of the new terms and phrases introduced raise definitional problems, notably the concept of a "business undertaking". The task of specifying the meaning of words and phrases used in the Charter has been left to the Cabinet, through an usually wide delegation of regulation-making power. However, the reconstructed French Language Board (Office de la langue française) has also been granted significant regulation-making authority, which may in some cases overlap with that of the Cabinet. The nature and extent of rights and obligations that seem to arise under the Charter may be difficult to ascertain. In particular, the effect or provisions as to the language of standard form contracts, and the manner of enforcing them, seem fraught with uncertainty. While the Charter obviously confirm the principles underlying the previous Official Language Act of 1974, it achieves greater clarity and consistency in stating those policies. In some respects, it allows for more flexibility than the earlier Act. The enforcement provisions of the Charter place greater emphasis on coercive action as regards the language of business. The Charter also breaks new ground by introducing a form of joint management of language conditions at work. In order to allow innovations to settle down, it is suggested that uncertainties be resolved by accumulated experience rather than through over-hasty amending legislation.